Broadening candidate office circumcision patients: A comparison of outcome in children based on age and weight. Issue 1 (February 2022) - Nicassio, Lauren; Klamer, Brett; Fuchs, Molly; McLeod, Daryl J.; Alpert, Seth; Jayanthi, Rama; DaJusta, Daniel; Ching, Christina B.
Summary: Introduction: Office circumcision with a clamp or Plastibell device is often restricted in practice by patient age and size. This is thought to ensure the patient fits appropriately on the restraining device and limit complications. Objective: To compare the outcomes of office circumcision in children ≤3 months of age and ≤5.1 kg in weight to those who do not fit this criterion. Study design: A retrospective chart review was performed of all office circumcisions in children ≤6 months of age performed in our urology clinic between January 2015–August 2018. Patients were divided into two groups: Group 1 (≤3 months old and ≤5.1 kg) and Group 2 (all others). Patient demographics and circumcision technique were recorded. The number of patients with complications and requiring an intervention related to circumcision were compared between groups, as well as the number of patients requiring unplanned hospital visits. Differences in outcomes were evaluated using Pearson's chi-square test. Results: A total of 205 circumcisions were performed in Group 1 and 498 circumcisions were performed in Group 2. All circumcisions were performed by either Gomco clamp or Plastibell device with no significant difference in method between groups (p = 0.5). There was no difference in median follow-up between groups (Group 1: 19 days [IQR 14; 34]; Group 2: 19 days [IQR 14; 36]; p = 0.6). There were no significant differences between groups in the number patients with complications or requiring an intervention (p = 0.08 and p = 0.12, respectively). Significantly more patients in Group 2 required an unplanned hospital visit (p = 0.02) (Table ). After categorizing those composing Group 2 into three disjoint sets (children >3 months and ≤5.1 kg, or ≤3 months and >5.1 kg, or >3 months and >5.1 kg), no significant difference across all four groups in regards to complications (p = 0.12) or intervention (p = 0.2) was found. There was a significant difference in unplanned hospital visits (p < 0.001). Discussion: Performing office circumcisions in children outside of age and weight restrictions of ≤3 months and ≤5.1 kg did not significantly increase the risk of complications or need for interventions. Those outside of age and weight restrictions, however, had more unplanned hospital visits. Tailoring parent expectations in this patient group may be needed. Conclusions: While we found older and heavier children had more unplanned post-procedural related hospital visits, their rates of overall complications and need for subsequent interventions were not significantly higher than younger and lighter children. Summary Table Comparison of outcomes between Groups 1 (≤3 months old and ≤5.1 kg in weight) versus Group 2 (>3 months or 5.1 kg). Summary Table Post-procedure course Group 1 (n = 205) Group 2 (n = 498) p-value Complication (%) 38 (19) 125 (25) 0.08 Intervention (%) 31 (15) 102 (20) 0.12 Unplanned hospital visits (%) 18 (9) 79 (16) 0.02 Office visits outside of planned follow-up (%) 14 (7) 50 (10) 0.18 ED/UC visits (%) 4 (2) 29 (6) 0.03 Patients with office phone calls (% patients) 45 (22) 115 (23) 0.60 Expected number of phone calls per patient 0.47 0.57 0.35